Evaluation the interaction of ABC multidrug transporter MDR1 with thymoquinone: substrate or inhibitor? - vahideh keyvani; Zeynab Naserifar; Mohammad-Reza Saberi; seyed ahmad mohajeri; Sepideh Arabzadeh; Farajollah Shahriari Ahmadi; Hossein Hosseinzadeh; Seyedeh Mahya Shariat Razavi; Fatemeh Kalalinia (Iranian Journal of Basic Medical Sciences, 2020)
Objective(s): Thymoquinone (TQ) has valuable medical properties like anticancer effects. Development of multidrug resistance (MDR) phenotype is one of the most important factors in failure of cancer chemotherapy. The aim of this study was to evaluate the mode of interaction of TQ and MDR1, a major MDR-related protein in gastric cancer drug resistant EPG85-257RDB cells, and its parental non-resistant EPG85-257 cells. Materials and Methods: MTT assay was used to assess the effects of TQ and doxorubicin (DOX) on cell viability of tested cell lines and TQ effect on pump performance. HPLC analyses were used to measure the input and output of TQ in EPG85-257RDB cells. Molecular docking studies were used to identify interactions between TQ and MDR1. Results: TQ inhibited cell viability in a time and concentration-dependent manner. Co-treatment of the cells with TQ and DOX did not significantly affect the amount of cell viability in comparison with DOX treatment alone. The HPLC analyses showed that more than 90% of TQ entered to EPG85-257RDB during 1 hr of treatment with TQ, but it was unable to exit from the cells. Moreover, there was no difference between influx and efflux amount of TQ in cells with inhibited and non-inhibited MDR1 transporters. Molecular docking studies revealed that TQ had a higher inhibitory constant to bind to active site of MDR1 protein as compared to specific inhibitor (verapamil) and substrate (vinblastine) of this transporter. Conclusion: These results proposed that TQ does not work as an inhibitor or a substrate of MDR1 transporter.